CONNECTION BETWEEN ECONOMICS, CULTURE AND CULTURAL DIPLOMACY - Valiyev, Agil (Annals of Spiru Haret University. Economic Series, 2017)
Today, culture is one of the main feeble factors of economic development. The leading role of culture in economic development should be argued as multiplied: so, on firstly, as domestic value, on secondly, as a main factor of regional economic development advanced to raised gravity of different regions for residents, tourists and investors, on thirdly, as major parameters of social development based on tolerance, creativity and knowledge. To the different international experiences, culture is main part of economic development in our life. Cultural diversities are combined into a main reason economic development model. The article consist of explainations about the understanding of culture, cultural diplomacy and economics, approach on conflicts between culture and economics, to find how affecting of culture to economic development, the role of culture in economic development of Azerbaijan. The article can be considered as a useful resource for experts and researchers conducting research in this field.